Community Empowerment Through PPK Ormawa To Strengthen Interest In Reading Rural Communities - Endi Rochaendi; Kana Safrina Rouzi; Eliza Dwinta; Nur Kholik; Indah Perdana Sari; Mahfud Mahfud; Baiq Ismiati (Universitas Andi Djemma, 2024)
Community service is a key activity of student organizations (Ormawa) to foster social awareness, empathy, and solidarity through science, technology, arts, and culture. The Student Organization Capacity Strengthening Program (PPK Ormawa), funded by the Directorate General of Higher Education, Research, and Technology, aims to enhance Ormawa's quality and develop students' soft skills and competencies. In 2023, HIMA PGSD/HIMMI of Alma Ata University received a grant to implement PPK Ormawa in Kalurahan Muntuk-Dlingo, Bantul Regency, focusing on boosting reading interest in rural communities. The activities included learning guidance to strengthen literacy and numeracy, utilizing the Service-Learning (S-L) method. Over four months, the program created a reading-friendly environment, formed regular reading groups, and developed STEAM-based learning modules. Post-test results showed significant improvement, with mastery levels increasing from 35% to 96% and the class average score rising from 64.28 to 89.96. PPK Ormawa successfully enhanced participants' literacy and numeracy understanding and built a lifelong learning environment. Future recommendations include updating literacy content, providing continuous training, conducting literacy campaigns, collaborating with educational institutions and local communities, and regular evaluations.